Avaliação antropométrica de pessoas transexuais: as estimativas de composição corporal baseadas no sexo biológico diferem daquelas adotadas no gênero autodeterminado? - Toscano, Leon Coelho (2021)
The transsexualizing process consists of several steps that may or may not take place over several years. Regardless of the stage a person is at, a complete nutritional assessment is an essential tool to help the health professional to conduct an adequate care routine for patients undergoing sexual transition. Therefore, the present study aims to evaluate whether the body composition based on Durnin and Womersley's (1974) 4-fold formula and bioimpedance, as well as muscle mass and ideal weight according to bone build, differ between biological sex and self-determined gender . This is a cross-sectional individualized observational study of a series of cases, which included 11 transsexuals, of both genders, with a mean age of 24.4 (4.2) years, at different stages of sexual transition. An individual anthropometric assessment was performed and data were pushed with the aid of the EpiData version 3.2® and SPSS version 20.0 softwares. The results of the study indicate that, of the parameters obtained, only in the estimation of percentage of body fat based on the 4 folds, there was a statistically significant difference between biological sex and self-determined gender (p-value in trans men = 0.018 and in trans women = 0.010 , using as a parameter p <0.05). It is concluded that when evaluating the value of gender and sex using the parameters portrayed in this study, there is no significant difference in the choice between one or the other, except for the %BF through the 4 folds, possibly not being the best alternative when it is about respecting a transsexual patient's sexual transition.